The Relationship of Breakfast Habits, Coffee Consumption, and Sleep Duration with Obesity Incidence in University Students - Nurul Putrie Utami; Cita Eri Ayuningtyas; Putri Cahya Pertiwi (Majalah Kesehatan Indonesia, 2023)
The increasing prevalence of adult obesity in Indonesia from 14,8 to 21,8% in 2013-2018 impacts in a higher incidence of various non-communicable diseases. Lifestyle changes such as sleeping habits, breakfast, exercise, and coffee consumption can escalate the risk of obesity. Purpose: The purpose of this study was to determine the relationship between breakfast habits, coffee consumption, and sleep duration with the incidence of obesity among Ahmad Dahlan University students. This study was an observational study with a cross-sectional design with a purposive sampling method. The subjects are 459 students of Universitas Ahmad Dahlan. The research instrument used was a self-administrated online questionnaire that asked about the habits of breakfast, sleep, and coffee consumption. Anthropometric data were obtained from the results of the latest anthropometric measurements of each research subject. The research data were processed using statistical applications using the chi-square test with a significance value of p <0.05. Results: Breakfast habits, frequency, sources, timing, and the menu was not related to nutritional status (p> 0.05). Other health habits such as sports habits and sleep duration also did not found any significant relationship with nutritional status (p> 0.05). However, coffee consumption was related to nutritional status (p = 0.001). This relationship was found in female subjects (p = 0.014). The conclusion of this study is that breakfast habits and sleep duration are not related to the nutritional status of students, while coffee drinking habits have a relationship with the nutritional status of students, especially female students.